Determinants of minimum acceptable diet among young children in an urban slum: a community-based study - Kunhipurayil, Kavita; Srivastav, Manissha (International Journal Of Community Medicine And Public Health, 2021)
Background: Child health and growth deteriorate as a result of inadequate quantities and frequencies of complementary feeding. Methods: A community-based cross-sectional study was conducted in urban field practice area of a tertiary medical college hospital among 280 children by systematic random sampling method. Children belonging to 12-23 months were included while sick child, children whose mother/guardian did not give consent were excluded. Results: The proportion of children who met the minimum dietary diversity (MDD) and minimum meal frequency (MMF) were 52.8 % (95% CI) and 52% (95% CI), respectively. Out of 280 children, 90 i.e. (32.1 %) children had achieved the recommended Minimum acceptable diet (MAD). Maternal education (Chi square value=11.2; CI 95%); socioeconomic status (Chi square value=57.4; CI 95%) were positively associated with dietary diversity. Higher percentage of male children (44.8 %) achieved minimum acceptable diet as compared to female children (20.5%); (chi square value=18.8, CI 95%). The percentage of children receiving MDD and MMF was more among children of higher socioeconomic class (p value 0.0001) and from nuclear family (p value=0.45). The birth order of the child was inversely related to the attainment of MAD. (p value=0.0001). Conclusions: Results of the study strongly suggest that poor dietary diversity and meal frequency is associated with numerous factors and their interplay is a multitude of combinations rather than a single cause.